100 Jahre Amharisch-Unterricht in Hamburg - Gerhardt, Ludwig (Aethiopica, 2019)
The article offers a spirited account of the 100-year-old history of teaching Amharic at the Universität Hamburg. It presents significant turning points in the fortunes of Amharic as a foreign language first taught in the Kolonialinstitut and then at the university, and portrays the people who shaped them, in particular the lectors of Amharic from Ethiopia. The account draws on archival documents interwoven with personal memories.